The impact of influencer-cause fit on the purchase intentions and brand attitude towards conscious brands in the fashion industry - Faria, Maria Angélico da Silva (2020)
Digital Influencers are taking advantage of social media rise to position themselves as effective brand communicators. Hence, brands are betting on Influencer Endorsement as a communication strategy, since it has been proved before how powerful that can be in shaping consumers’ choices. Additionally, the market for sustainable fashion brands is gaining strength due to the raising of social and environmental concerns. However, brands are facing the challenge of choosing the right Influencer to endorse them since not all fit the brand and the product. This research aims to understand the impact that a high-fit between the Influencer and the Cause, as opposed to low-fit, has on Purchase Intention and Brand Attitude towards conscious fashion brands. Moreover, this study explores how do these effects take place with Source Credibility, Source Attractiveness, Product Match-up, and Meaning Transfer being analyzed. An experimental design was implemented to test and compare the differences between high versus low Influencer-cause fit, through an online questionnaire, and 335 valid responses were collected. The main findings show that Influencer’s high-fit with the cause has a higher and significant effect on Purchase Intention and Brand Attitude. Moreover, Source Credibility, Source Attractiveness, and Meaning Transfer are positive and significantly correlated with Purchase Intention and Brand Attitude. Regarding Product Match-up, it is positive and significantly correlated with Purchase Intentions but not with Brand Attitude. Lastly, Source Attractiveness cannot be a possible explaining factor for Brand Attitude since it did not present a significantly higher effect on the high-fit scenario for this construct.